Environmental objectives and targets / Nurzawani Md Sofwan ... [et al.] - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Emeih Wahed, Wan Juliana; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Elna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
UiTMCS has set a number of environmental goals and targets to improve the organisation's environmental performance and support the university's environmental sustainability agenda. The priority of environmental aspects highlighted on campus are given special attention. Table 4.4 summarizes the environmental objectives and its respective targets.